THE RELATIONSHIP BETWEEN TEACHERS’ PROFESSIONAL COMPETENCIES AND THE ACHIEVEMENT OF GRADUATE COMPETENCY STANDARDS IN ELEMENTARY SCHOOLS - Razak, Faisal; Idris, Haziq; Som, Rit; Purnomo, Widiharto (Yayasan Adra Karima Hubbi, 2025)
The quality of elementary education is fundamentally linked to teacher effectiveness, with professional competence being a cornerstone of student success. This study aimed to quantitatively determine the relationship between the professional competencies of elementary school teachers and the achievement of Graduate Competency Standards (GCS) by their students. A quantitative correlational design was employed, involving a sample of certified teachers and their respective students from several elementary schools. Teacher professional competence was assessed using a standardized competency test, while student achievement data was obtained from official GCS scores. The data were analyzed using Pearson correlation. The results revealed a significant and strong positive correlation (r = 0.78, p < 0.01) between the level of teachers’ professional competence and students’ GCS achievement. Higher teacher competence scores were consistently associated with higher student achievement. This study concludes that teachers’ professional competence is a critical and significant predictor of students’ success in meeting educational benchmarks. Therefore, enhancing the quality of elementary education hinges on targeted and continuous professional development programs for teachers.